PENGARUH PENGEMBANGAN KARIR DAN BALAS JASA TERHADAP KINERJA PEGAWAI - bahrudi efendi damanik (Politeknik Bisnis Indonesia, 2018)
The purpose of this study was to determine the effect of career development on employee performance, to find out how the effect of remuneration on employee performance, to find out how the influence of career development and remuneration simultaneously on employee performance. The method used is the survey method and data collection carried out through observation, interviews, and distributing questionnaires using a Likert scale as a measuring device. The study was conducted at the Revenue Service Office of North Sumatra Province UPT Pematangsiantar, the sample in this study amounted to 36 employees, the data analysis technique used was multiple linear analysis techniques. The results of the research obtained are career development and remuneration variables simultaneously have a positive and significant effect on employee performance, with Fcount> Ftable (15,170> 3,230), the partial return variable has a positive and significant effect on employee performance, with a tcount value> table (2,416> 2,021), partial career development variable has a positive and significant effect on employee performance, with a value of tcount> ttable (2,094> 2,021), R square value of 0,479, this indicates that 47.90% of career development variables and remuneration are simultaneous effect on the performance of employees in the Revenue Service of North Sumatra Province UPT. Pematangsiantar, while the remaining 52.10% influenced by other variables not examined